Database-Oriented Sports Competition Information Management Intelligent Retrieval System Based on Computer Multi-Heterogeneous Disaster Recovery Backup - Chen, Kefang (2022 6th International Conference on Trends in Electronics and Informatics (ICOEI), 2022)
Using the FC/IP and compression transmission technology of SAN Router, the application scope of IBM SVC virtual storage technology in data disaster recovery and backup has been expanded. Features, establish three sub-databases of athletes, referees and coaches, and establish a data link mapping table, according to different data collection channels such as sports competitions, professional leagues and sports school training, realize data storage timelines, intelligent retrieval. The whole system uses the SSH development framework, uses SQL SEVER as the database software, and has been testedin practice.